Istidraj in the Qur'an, Surah Al-An'am, Verse 44: Perspective of Ibnu Katsir's Tafsir - Putri, Aisyah Cendikia; Nugroho, Kharis (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research discusses the interpretation of the istidraj verse in the Qur'an, especially in the letter Al-An'am Verse: 44 in Tafsir Ibn Kathir, which discusses those people who do not believe and forget the warning that has been given to them, and because deny the verse and become complacent about it, Allah opens the door to pleasure for them, without them realizing it, they are given a sudden punishment, and at that time they can only remain silent and despair, and in this research also discusses several verses in The Qur'an discusses that Istidraj brings destruction.‏ (QS. Al A'raf; 95-96), The method used in this research uses a qualitative descriptive approach, qualitative research is a type of research whose results are not obtained through statistical procedures and aims to reveal overall objectives with data collection and the researcher himself as the main instrument. The results of this research are that first, according to Ibnu Katsir, Istidraj is those who are deceived by the doors of sustenance that Allah opens in all aspects of life. The second is punishment for the people of Istidraj with sudden torture until they are people who do not believe and who are negligent until they despair.